Aplikasi Bakteri Probiotik melalui Pakan Buatan untuk Meningkatkan Kinerja Pertumbuhan Udang Windu (Penaeus monodon) - Widanarni Widanarni; Dinamella Wahjuningrum; Fiska Puspita (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2012)
This research was conducted to study the effect of probiotic bacteria application through artificial feed on growth performance of tiger shrimp. The research was carried out for 42 days with four treatments and three replications, those were control, SKT-b (feed + SKT-b probiotic), 1 UB (feed + 1 UB probiotic) and commercial (feed + commercial probiotic). Feed and probiotic bacteria were mixed in ratio of 3:1 (weight : volume) by adding 3 % of white egg as a binder.  Then the test feed was analyzed by proximate analyses and compared by using control feed. Tiger shrimps with initial weight of 0.04 ± 0.005 g were reared in 50 cm x 40 cm  x 40 cm aquaria at the density of 15 shrimps per aquarium.  Feeding was carried out four times a day at 08.00, 12.00, 16.00, and 22.00. The weight of tiger shrimp were observed once every 2 weeks, whereas the water quality and the total abundance of bacteria in media were monitored at the beginning, middle and end of the research.The result showed that theadministration of the probiotic bacteria through artificial feed produced better growth rate than control. Application of 1 UB probiotic gave the best results by producing 9.03% growth rate and 1.35feed conversion ratio. Whereas, survival rates for all treatments were not significantly different from the range of values between 91.11% - 97.78%.Keywords: probiotic bacteria, feed, tiger shrimp